A non-represing model of identity grounded in the genre of oral auto/biography by women - Barát, Erzsébet (Cadernos de Linguagem e Sociedade, 2010)
My paper is an attempt at the theorisation of identity from a materialist feminist perspective, drawing on the oral life narratives of Hungarian women. I would like to contribute to the ongoing debates on the limits and value of identity politics for feminist political and ethical objectives. In my view identity is a discursive construct that is never finished but aspires to momentary cohesion. The basic social conditions for such a Self is multiplicity and equivalent relations of power. Such a non-repressive model entails two major changes to exclusionary conceptualisations of identity. One is the recognition of the connectedness of the Self to the Other, that is the intersubjective nature of the Self. The other is difference, heterogeneity within the Self that is the condition for the former. As a discursively mediated practice of telling a life, auto/biography is understood to be the narrative site for making sense of the Self. Its major function is to construct a coherent Self out of the heterogeneous socio-cultural positionings available at any particular moment of telling. This sense of temporay coherence is achieved through the articulatory practices of the genre, that is, through the narrative device of emplotment. My data consists of eight life-span narratives shared with me by eight woman friends of mine. I analyse one of them, the life narrative by Adél, in detail for a case study. I shall focus on the analysis of the dilemma of a relational identity which all these narratives are re/constructing as their central theme. The dilemmas are all formulated from a gendered position problematising the limits of being a woman in contemporary Hungarian society. My major interest in the analysis is to see whether it is possible for Adél, to subvert, or transform even, the dominant hegemonic relations of power.